PENGENDALI SUHU RUANGAN BERDASARKAN JUMLAH ORANG DALAM RUANGAN BERBASIS INTERNET OF THINGS - Rika E. Butarbutar; Agus Triyono; Budi Utomo (Jurnal Riset Sistem Informasi, 2025)
This research entitled "Internet of Things-Based Room Temperature Control Based on the Number of Occupants in a Room," aims to design and implement a room temperature control system that is responsive to the number of occupants in a room, using Internet of Things (IoT) technology. In this modern era, the need for thermal comfort in workspaces is increasingly important, especially in the context of efficient work environments. The proposed system utilizes ultrasonic sensors to detect the number of occupants and DHT22 sensors to monitor temperature and humidity. The collected data is then used to automatically adjust temperature settings, thereby creating a comfortable and energy-efficient environment. The results show that this system can improve occupant comfort and optimize energy use. Furthermore, integration with the ThingsBoard platform allows remote temperature monitoring and regulation, providing additional flexibility for users. Thus, this research is expected to provide an innovative solution for smarter and more efficient room temperature control.